Multivariate decoding methods reveal how speaking two dialects affects executive functions - Yan Jing Wu, Qinpu Dang, Zhaoqi Zhang, Haoyun Zhang, Taomei Guo (European Journal of Neuroscience, 2023)
How speaking two languages affects executive functions has been a long-standing debate and the mechanisms underlying the observed cognitive advantages of bilingualism remain unspecified. Here, using multivariate pattern classification methods, we decoded spatial patterns of neural signals associated with Flanker task performance in mono-dialectal and bi-dialectal speakers of Chinese. While univariate approach to even-related potentials (ERPs) showed no between-group difference, decoding accuracy of ERPs was reduced in bi-dialectal as compared to mono-dialectal speakers in both congruent-neutral and incongruent-neutral classifications. There was no effect of bidialectalism, however, on decoding accuracy of alpha-band oscillations, an electrophysiological index implicated in inhibition. Behavioural data analysed using the Drift Diffusion Model (DDM) showed facilitating effects of bidialectalism on non-decision times but no effect on drift rates. These findings demonstrate that using two dialects on a daily basis enhances general attentional deployment rather than affecting specific component of executive functions such as inhibitory control. Given that the two dialects of Chinese differed almost exclusively in phonology, the bidialectalism effect was most likely motivated by resolving phonological competition at lexical processing level.